DOZ047.108: Utilizing dynamic CT imaging to map tissue regeneration in a porcine model of esophageal loss. (24th June 2019) - Jensen, T; Sharma, I; Fodor, W; Sundaram, S; Roffidal, T; Finck, C
Abstract: Esophageal atresia (EA) is a congenital defect in which the esophagus is not fully connected. Current treatments to bring together long gaps between the esophagus have very high complication rates and the replacement tissue does not possess the correct structure or physiologic properties. Tissue engineering and regenerative medicine have been suggested as a new patient-specific treatment for EA utilizing the patient's own cells and a tubular scaffold. Our group recently published on the successful regeneration of an esophagus using a retrievable scaffold seeded with amniotic derived MSCsFurther evaluation with dynamic computed tomography has suggested that the regenerative process entails ingrowth of native esophageal cells from both proximal and distal ends including robust vascular ingrowth. This confirms our gene expression findings and lends support to our hypothesis that the regenerative process is driven by vascular ingrowth. The role of the cells seeded on esophageal scaffolds and how this affects the regenerative process is the focus of current investigation with animal studies that are ongoing.